Reconceptualization Of Legal Protection Against Medical Malpractice Through The Integration Of Artificial Intelligence Technology - Rommy Sebastian Koto; Megawati Barthos (Jurnal Multidisiplin Indonesia, 2025)
Technological developments, especially artificial intelligence (AI), now present challenges as well as opportunities for legal practice in various sectors. This paper examines how AI integration can reformulate the legal protection paradigm in the context of business law, with particular application to cases of medical malpractice related to inaccuracies in diagnosis and surgical procedures. By combining theoretical analysis and case approaches, this study offers a reconceptualization of legal accountability mechanisms. The proposed new model aims to support a more adaptive, inclusive, and justice-based legal protection system, in line with the ongoing digital transformation. The paper also touches on the initial findings in a dissertation that reviews the medical aspects, as a basis for integrating technological innovations into the business legal framework to improve operational standards and law enforcement effectiveness. The implications of integrating AI are expected to not only stimulate policy reform in the health sector, but also provide a foundation for the development of innovative legal models in the digital age.